Pendekatan Analisis Vector Error Corretion Model (VECM) Dalam Hubungan Pertumbuhan Ekonomi Dan Sektor Pariwisata - Dio Dwi Saputra; Afifah Sukmawati (Seminar Nasional Official Statistics, 2021)
Riau Islands Province is one of the gateways for foreign tourists to enter Indonesia. The current condition of the Covid-19 pandemic has made the tourism sector in the Riau Islands Province experience a slump. On the other hand, economic growth was also affected, where conditions were lower than national economic growth. Thus, this study was conducted to determine whether there is a relationship between economic growth and the tourism sector in the Riau Islands Province. The variables used are the year-on-year growth of Gross Regional Domestic Product to represent indicators of economic growth (EKO); the number of foreign tourists visiting (WISMAN), the average occupancy rate of five-star hotel rooms (TPK) and the realization value of foreign investment in the hotel and restaurant sector (INVEST), which represent indicators of the tourism sector. This study applies descriptive analysis (graphics of time series data) and inferential (Vector Error Correction Model). The results showed that there was no Granger causality relationship between economic growth and the tourism sector, however, when viewed based on the IRF graphs and FEVD, it showed that there was a relationship between the response of economic growth to shocks that occurred in the tourism sector. The economic growth of the Riau Islands Province will respond to shocks that occur in the tourism sector in a relatively short time (only up to the 20th to 25th period). This means that the government must continue to provide stimulus in the tourism sector continuously in a not too long period of time, so that economic growth can continue to move as expected.